Mechanical behavior of bioactive poly(ethylene glycol) diacrylate matrices for biomedical application. (October 2020) - Della Sala, Francesca; Biondi, Marco; Guarnieri, Daniela; Borzacchiello, Assunta; Ambrosio, Luigi; Mayol, Laura
Abstract: The biomedical applications of physically entangled polymeric hydrogels are generally limited due to their weak mechanical properties, rapid swelling and dissolution in physiologically relevant environment. Chemical crosslinking helps stabilizing hydrogel structure and enhancing mechanical properties, thereby allowing a higher stability in phisiological environment. In this context, it is known that the mechanical properties of the hydrogel are affected by both the molecular weight (MW) of the starting polymer and the concentration of the crosslinker. Here, our aim was to assess the influence of polymer MW and concentration in the precursor solution on the mechanical features of the final hydrogel and their influence on cells-material interaction. In detail, 3D synthetic matrices based on poly(ethylene glycol) diacrylate (PEGDA) at two molecular weights (PEG 700 and PEG 3400) and at three different concentrations (10, 20, 40 w/v %), which were photopolymerized using darocour as an initiator, were studied. Then, infrared and swelling analyses, along with a comprehensive mechanical characterization of the obtained hydrogels (i.e. oscillatory shear and confined compression tests), were performed. Finally, to evaluate the influence of the mechanical features on the biological behaviour, the hydrogels were characterized in terms of cell adhesion percentage and cell viability after functionalizing the substrates with RGD peptide at three different concentrations. Results have demonstrated that both the Young's modulus (E) in compression and the elastic modulus (G') in shear of the hydrogels increase with increasing polymer precursor concentration. E decreased as MW increased, and the differences are more relevant for more concentrated hydrogels. On the contrary, G' appears to increase with increasing PEGDA MW and in particular for the lowest polymer precursor concentration. The biological results have demonstrated that cells cultured for longer times seem to prefer PEG 3400 hydrogels with a larger mesh size structure that posses higher viscoelastic properties in shear. Graphical abstract: Image 1 Highlights: Hydrogels based on poly (ethylene glycol) diacrylate (PEGDA) were produced. PEG 700 and 3400 Da at (10, 20, 40 w/v %) were photo-polymerized using darocour. Oscillatory shear and confined compression tests on hydrogels as mechanical test. Hydrogels functionalized at 0.5, 1, 5 mM of the RGD peptide. Higher vitality of NIH 3T3 cells in presence of PEG 3400 hydrogel at longer times.